Transição metal-isolante e correções para a condutividade no grafeno bombardeado por feixe de íons de hélio - Eduardo Nery Duarte de Araujo (2015)
Theoretical works have been proposed that the production of a periodic potential on the graphene may allow the control of the electric current, without the need of cuts in the material or external waveguides. Inspired by these works, we have fabricated graphene devices in Hall bar shapes which had different regions of the conduction channel modified by nanometric patterns. These patterns consisted in strips with tens of nanometers that were produced by irradiation of graphene by a 30 KeV helium ions beam. The transport proprieties in each region were investigated by measuring the magnetoconductivity for different carrier densities and temperatures. We studied the effect of disorder on the electrical transport properties as one goes progressively, from a pristine region to a highly bombarded graphene region of the device. Our results have shown a transition from diffusive transport, in which electrons are weakly localized in a metallic regime, to a variable-range hopping transport, in which electrons are strongly localized in an insulating regime, as one goes from the pristine to the most bombarded graphene region. By analyzing the magnetoconductivity of different regions, we have obtained the characteristic scattering times of charge carriers in graphene. These results have shown that at low temperatures the electron-electron scattering is more important than electron-phonon scattering to explain the linear behavior of phase-relaxation rate with temperature. We have also shown that the intervalley scattering rate increases with the density os defects strips. We have studied the corrections to conductivity in graphene at zero magnetic field beyond the classical Drudes model. Our results indicate that the electron-electron interaction is sufficient to describe the conductivity correction only for the pristine graphene region. However, for the bombarded regions, the Kondo effect must be added to explain the logarithmic behavior of the conductivity with temperature.